Methodological lessons on measuring quality teaching in Southern contexts, with a focus on India and Pakistan. (March 2019) - Aslam, Monazza; Malik, Rabea; Rawal, Shenila; Rose, Pauline; Vignoles, Anna; Whitaker, Lydia
Quantifying the impact of teaching quality on pupil learning, and understanding what teacher characteristics or practices are likely to improve student achievement, are pressing research questions in all countries. Empirical evidence also needs to be context specific since different education systems are likely to have different facilitators and barriers to good teaching. Existing evidence, largely from the US, suggests a number of strong research designs that enable researchers to model the impact of teaching on pupil achievement. However, operationalising these models in more resource-constrained contexts is challenging. In this paper we describe our attempt to model the impact of teachers and their practices on pupil achievement using the quantitative data generated for this research (household and school surveys with a teacher survey and an attempt to assess teacher knowledge). We describe the challenges when trying to implement this approach in the Indian and Pakistan context and the methodological adaptions needed. We reflect on the strengths and weaknesses of our approach. We note that existing literature tends to provide relatively minimal descriptions of the specific research design and instruments used to model teacher quality and hence provides a partial picture of methodological considerations. In this paper we contribute a detailed and frank account of developing a workable research design and the challenges we encountered.